Cycling efficiency and performance following short-term training using uncoupled cranks - Williams, A. D.; Raj, I. S.; Stucas, K. L.; Fell, J. W.; Dickenson, D.; Gregory, J. R. (International Journal of Sports Physiology and Performance, 2009)
Objectives: Uncoupled cycling cranks are designed to remove the ability of one leg to assist the other during the cycling action. It has been suggested that training with this type of crank can increase mechanical efficiency. However, whether these improvements can confer performance enhancement in already well-trained cyclists has not been reported. Method: Fourteen well-trained cyclists (13 males, 1 female; 32.4 ± 8.8 y; 74.5 ± 10.3 kg; VO2max 60.6 ± 5.5 mL/kg·min; mean ± SD) participated in this study. Participants were randomized to training on a stationary bicycle using either an uncoupled (n = 7) or traditional crank (n = 7) system. Training involved 1-h sessions, 3 days per week for 6 weeks, and at a heart rate equivalent to 70% of peak power output (PPO) substituted into the training schedule in place of other training. VO2max, lactate threshold, gross efficiency, and cycling performance were measured before and following the training intervention. Pre- and posttesting was conducted using traditional cranks. Results: No differences were observed between the groups for changes in VO2max, lactate threshold, gross efficiency, or average power maintained during a 30-minute time trial. Conclusion: Our results indicate that 6 weeks (18 sessions) of training using an uncoupled crank system does not result in changes in any physiological or performance measures in well-trained cyclists.